Dancers in ceremonial dress at a Tlingit potlatch, Klukwan, Alaska, October 15, 1898 - Hegg, Eric A., 1867-1948 (1898)
Stick Indians also know as Tagish Indians. Caption on image: "Dance given by the Stick's at the potlach at Klukwan. Oct 15 '98